Traumatic retroperitoneal hematoma. About 35 cases - Cassinelli, Fernando; Alonso, Oscar; Amorín, Rosario; Morelli, Raúl (Cirugía del Uruguay, 1999)
35 cases of traumatic retroperitoneal hematoma from the !CU registry at Pasteur Hospital were analysed as regards age, gender, lesiona! mechanism, type of trauma (open-closed), presence of shock, transfusion needs, associated injuries and treatment. Hematomas were classified into five types according to the classification of the Argentine Association of Surgery Out of the 35 cases, 21 were open trauma {60%) and 14 were closed (40%).